2010
DOI: 10.1128/aem.03025-09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Characteristics on the Diversity of Bacteria in the Southern Brazilian Atlantic Forest

Abstract: The Brazilian Atlantic Forest is one of the 25 biodiversity hot spots in the world. Although the diversity of its fauna and flora has been studied fairly well, little is known of its microbial communities. In this work, we analyzed the Atlantic Forest ecosystem to determine its bacterial biodiversity, using 16S rRNA gene sequencing, and correlated changes in deduced taxonomic profiles with the physicochemical characteristics of the soil. DNAs were purified from soil samples, and the 16S rRNA gene was amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
88
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(108 citation statements)
references
References 35 publications
8
88
0
7
Order By: Relevance
“…Specifically, the concentrations of aluminum were strongly related to the abundance of members within the family Chitinophagaceae. Aluminum has been previously shown to affect the diversity of bacteria in agricultural soils (37) and to be linked to changes in bacterial diversity in forest ecosystems (38). However, it is important that the concentrations of aluminum were correlated with the concentrations of several other heavy metals (Table S3).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, the concentrations of aluminum were strongly related to the abundance of members within the family Chitinophagaceae. Aluminum has been previously shown to affect the diversity of bacteria in agricultural soils (37) and to be linked to changes in bacterial diversity in forest ecosystems (38). However, it is important that the concentrations of aluminum were correlated with the concentrations of several other heavy metals (Table S3).…”
Section: Discussionmentioning
confidence: 98%
“…Determination of the stereochemistry of the glycerol moieties in these molecules revealed that they must derive from Bacteria (50), possibly Acidobacteria (49). The natural 13 C abundance of these bacterial tetraethers in soil is consistent with a heterotrophic lifestyle of its source organism(s) (53). Examination of a suite of bacterial cultures, including a few acidobacterial strains, for the bacterial tetraethers did not reveal their origin (49).…”
mentioning
confidence: 83%
“…Percent soil moisture (⍜) was determined gravimetrically after oven drying. Soil pH was determined by combining 10 g soil with 10 ml deionized H 2 O. Nitrogen and carbon content were determined by using dry combustion on a Carlo-Erba C/N analyzer, and phosphorus (6,14), alpine hyper arid soils (9), hot desert (8,39,47), alpine tundra (37), Antarctic peninsula/coastal (6, 45), semiarid soils (1, 26, 32), prairies/grasslands (12, 41), pasture (22), crop agriculture (7,22,29,41,50), temperate forest (17,22,29,30,41), tropical forest (13), moist acidic tundra (5), and freshwater sediments (27,48 . Fibrobacter succinogenes was used as an outgroup.…”
mentioning
confidence: 99%